Uncovering Robust Delactoylase and Depyruvoylase Activities of HDAC Isoforms - Zessin, Matthes; Meleshin, Marat; Praetorius, Lucas; Sippl, Wolfgang; Bařinka, Cyril; Schutkowski, Mike (ACS chemical biology, 2022)
Zinc-dependent histone deacetylases (HDACs) and sirtuins (SIRT) represent two different classes of enzymes which are responsible for deacylation of modified lysine side chains. The repertoire of acyl residues on lysine side chains identified in vivo is rapidly growing, and very recently lysine lactoylation was described to be involved in metabolic reprogramming. Additionally, lysine pyruvoylation represents a marker for aging and liver cirrhosis. Here, we report a systematic analysis of acyl-specificity of human zinc-dependent HDAC and sirtuin isoforms. We identified HDAC3 as a robust delactoylase with several-thousand-fold higher activity as compared to SIRT2, which was claimed to be the major in vivo delactoylase. Additionally, we systematically searched for enzymes, capable of removing pyruvoyl residues from lysine side chains. Using model peptides, we uncovered high depyruvoylase activity for HDAC6 and HDAC8. Interestingly, such substrates have extremely low KM values for both HDAC isoforms, pointing to possible in vivo functions.
Keywords: Aging; Histone Deacetylase Inhibitors; Histone Deacetylases; zinek; Lysine; Sirtuin 2; lysin; lidé; protein - isoformy; Zinc; Repressor Proteins; histondeacetylasy; Protein Isoforms; represorové proteiny; stárnutí; sirtuin 2; inhibitory histondeacetylas; Humans